Bacterial profiles and their antibiotic susceptibility patterns in neonatal sepsis at the University of Gondar Comprehensive Specialized Hospital, Ethiopia - Deress, Teshiwal; Belay, Gizeaddis; Ayenew, Getahun; Ferede, Worku; Worku, Minichile; Feleke, Tigist; Mulu, Meseret; Belay, Solomon; Getie, Michael (Frontiers in Microbiology, 2024)
Background Neonatal sepsis is a major cause of morbidity and mortality worldwide. Understanding the bacterial profiles and antibiotic susceptibility patterns causing neonatal sepsis is crucial for guiding appropriate treatment, improving patient outcomes, and combating the emergence of antibiotic resistance. Despite its importance, data regarding neonatal sepsis in the study area is limited. Therefore, this study aimed to characterize the bacterial pathogens and identify associated factors among neonates with suspected sepsis at the University of Gondar Comprehensive Specialized Hospital, Ethiopia. Methods A cross-sectional study was conducted by reviewing laboratory records of neonates admitted for suspected sepsis from January 2019 to December 2021. Data were checked for completeness and encoded in a spreadsheet program. Then, data were exported to STATA version 17 for analysis. Descriptive statistics such as frequency and percentage were computed. The association between neonatal sepsis and potential risk factors was assessed using Pearson’s chi-square test. A p-value of < 0.05, was considered statistically significant. Results A total of 1,236 neonates were included. Of these, 96.2% (1,190/1,236) had a fever before admission. The prevalence of culture-confirmed sepsis was 25.4% (314/1,236). Bacterial pathogens accounted for 23% (284/1,236) of these isolates, with Gram-negative bacteria being more prevalent at 75.3% (214/284) than Gram-positive bacteria at 24.7% (70/284). The most frequently isolated bacterial pathogens were K. pneumoniae 38.7% (110/284) and S. aureus 13% (37/284). The isolates demonstrated a high resistance level to commonly used antibiotics, with 61.6% exhibiting multidrug resistance. K. pneumoniae showed the highest rate of multidrug resistance (90.9%). Neonatal sepsis was associated with several factors, including fever before and after admission, hypothermia, increased respiration, suspected pneumonia, and suspected meningitis. Conclusion This study identified a high prevalence of culture-confirmed sepsis in neonates at UoGCSH, with Gram-negative bacteria, especially K. pneumoniae, dominating the isolated pathogens. The isolated bacteria exhibited alarming resistance to commonly used antibiotics, with a high proportion demonstrating multidrug resistance. Implementing effective antibiotic stewardship programs is crucial to optimize antibiotic use, reduce unnecessary prescriptions, and curb the spread of resistant strains.